Fabrication of an α-MoO3 nanobelt membrane showing a three-dimensional cross-linked nano-scale network structure for water and oil mixture separation. Issue 35 (18th April 2015) - Ma, Zhong-Chao; Wang, Li-Min; Chu, De-Qing; Sun, Hong-Ming; Wang, Ao-Xuan
<x xml:space="preserve">Abstract</x> An α-MoO3 nanobelt membrane with amphiphilic properties has been successfully fabricated via a hydrothermal method. The wetted membrane could be applied for the separation of nonpolar liquids and water.